The sustainable agriculture imperative: A perspective on the need for an agrosystem approach to meet the United Nations Sustainable Development Goals by 2030. (16th December 2021) - Shahmohamadloo, René S.; Febria, Catherine M.; Fraser, Evan D. G.; Sibley, Paul K.
Abstract: The development of modern, industrial agriculture and its high input–high output carbon energy model is rendering agricultural landscapes less resilient. The expected continued increase in the frequency and intensity of extreme weather events, in conjunction with declining soil health and biodiversity losses, could make food more expensive to produce. The United Nations has called for global action by establishing 17 sustainable development goals (SDGs), four of which are linked to food production and security: declining biodiversity (SDG 15), loss of ecosystem services and agroecosystem stability caused by increasing stress from food production intensification and climate change (SDG 13), declining soil health caused by agricultural practices (SDGs 2 and 6), and dependence on synthetic fertilizers and pesticides to maintain high productivity (SDG 2). To achieve these SDGs, the agriculture sector must take a leading role in reversing the many negative environmental trends apparent in today's agricultural landscapes to ensure that they will adapt and be resilient to climate change in 2030 and beyond. This will demand fundamental changes in how we practice agriculture from an environmental standpoint. Here, we present a perspective focused on the implementation of an agrosystem approach, which we define to promote regenerative agriculture, an integrative approach that provides greater resilience to a changing climate, reverses biodiversity loss, and improves soil health; honors Indigenous ways of knowing and a holistic approach to living off and learning from the land; and supports the establishment of emerging circular economies and community well‐being. Integr Environ Assess Manag 2022;18:1199–1205. © 2021 SETAC Key Points: The agrosystem approach promotes regenerative agriculture, an integrative approach that can provide greater resilience to a changing climate, reverse biodiversity loss, and improve soil health. The agrosystem approach honors Indigenous ways of knowing and a holistic approach to living off and learning from the land The agrosystem approach supports the establishment of emerging circular economies and community well‐being